Microbial contamination of equipment in the dental laboratory - Cheong, Joo Ming; Hussin, Akbar Sham; Ichwan, Solachuddin J. A.; Khalid, Rafiq; Abidin, Sulhi (2013)
Objectives: To determine the extent of microbial contamination on the high touch areas of equipment in the dental laboratory. Method: A dental laboratory based cross-sectional study was carried out on four selected high touch areas, which were the vibrator (power switch), the cast trimmer (power switch) and the denture polisher (power switch & speed control knob). Sterile cotton swabs were used to swab these four areas, smeared onto nutrient agar media and then incubated for 72 hours. The colony forming units (CFU) were counted after 72 hours to determine the extent of microbial contamination. Sample collection was carried out for 3 consecutive days. As a control, the same areas were disinfected and samples were taken exactly as before. Investigation of similar procedure was carried out for another week. A total of 48 sample plates were collected, 24 before disinfection and another 24 after disinfection. Results: A before and after comparison of mean CFU count in the four high touch areas showed both speed control knob (216/54.33) and power switch (189.67/9.83) of the denture polishing machine had the highest CFU count, followed by the cast trimmer (68.17/18) and finally the vibrator (50/7). Before disinfection, the minimum, maximum and mean ± SD bacteria count in 24 plates were 19, 410 and 131.08 ± 105.77 respectively. The minimum, maximum and mean ± (SD) bacteria count in 24 plates after disinfection were 1, 102 and 21.96 ± 28.303 respectively. Reduction in mean of CFU count after surface disinfection using paired T-test was statistically significant (p<0.05). Conclusion: There is high level of bacterial contamination of the high touch areas in the absence of surface disinfection. Therefore, disinfection procedures as are conducted in dental clinic should be implemented in the dental laboratory. Keywords: Dental laboratory, High touch areas, Bacterial contamination, Disinfection